Biology and Management of Chinese Tallow Tree - Rick Williams; Patrick Minogue (EDIS, 2008)
FOR-190, a 3-page illustrated fact sheet by Rick Williams and Patrick Minogue, describes this noxious weed introduced originally for oil production and favored as an ornamental, its biology and management strategies. Published July 2008.